Antinutritional factors, nutritional improvement, and future food use of common beans: A perspective - Cominelli, Eleonora; Sparvoli, Francesca; Lisciani, Silvia; Forti, Chiara; Camilli, Emanuela; Ferrari, Marika; Le Donne, Cinzia; Marconi, Stefania; Juan Vorster, Barend; Botha, Anna-Maria; Marais, Diana; Losa, Alessia; et al. (Frontiers in Plant Science, 2022)
Common bean seeds are an excellent source of protein as well as of carbohydrates, minerals, vitamins and bioactive compounds reducing, when in the diet, the risks of diseases. The presence of bioactive compounds with antinutritional properties (e.g. phytic acid, lectins, raffinosaccharides, protease inhibitors) limits, however, the bean’s nutritional value and its more widely use in food preparations. In the last decades, concerted efforts have been, therefore, made to develop new common bean genotypes with reduced antinutritional compounds by exploiting the natural genetic variability of common bean and also applying induced mutagenesis. However, possible negative, or positive, pleiotropic effects due to these modifications, in terms of plant performance in response to stresses or in the resulting technological properties of the developed mutant genotypes, have yet not been thoroughly investigated. The purpose of the perspective paper is to first highlight the current advances, which have been already made in mutant bean characterization. A view will be further provided on future research directions to specifically explore further advantages and disadvantages of these bean mutants, their potential use in innovative foods and representing a valuable genetic reservoir of combinations to assess the true functional role of specific seed bioactive components directly in the food matrix.